2019
DOI: 10.3389/fphy.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

The Symmetry Energy of the Nuclear EoS: A Study of Collective Motion and Low-Energy Reaction Dynamics in Semiclassical Approaches

Abstract: In the framework of mean-field based transport approaches, we discuss recent results concerning collective motion and low-energy heavy ion reactions involving neutron-rich systems. We focus on aspects which are particularly sensitive to the isovector terms of the nuclear effective interaction and the corresponding symmetry energy. As far as collective excitations are concerned, we discuss the mixed nature of dipole oscillations in neutron-rich systems. On the other hand, for reactions close to the Coulomb barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
(133 reference statements)
1
9
0
Order By: Relevance
“…Again the determination of higher value of F sym,0 along with K 0 by NL3 forces suggested that we need a better parameterized EoS, so that we can match the prediction of nuclear parameters made by various theoretical and experimental studies. On the other hand, the spectrum of F sym at finite temperature determined by our recently developed G3 parameter and the popular IU-FSU, fall in the expected range which is verified by other studies also [42,[56][57][58][59]. L sym changes slightly as we change the temperature for NL3 parameter set, while for G3 and IU-FSU it remains unaffected.…”
Section: Resultssupporting
confidence: 86%
“…Again the determination of higher value of F sym,0 along with K 0 by NL3 forces suggested that we need a better parameterized EoS, so that we can match the prediction of nuclear parameters made by various theoretical and experimental studies. On the other hand, the spectrum of F sym at finite temperature determined by our recently developed G3 parameter and the popular IU-FSU, fall in the expected range which is verified by other studies also [42,[56][57][58][59]. L sym changes slightly as we change the temperature for NL3 parameter set, while for G3 and IU-FSU it remains unaffected.…”
Section: Resultssupporting
confidence: 86%
“…( 4) and ( 6) that L is a measure of the slope of the NM EoS at saturation density since the SNM EoS has a vanishing slope at that point, by definition of saturation. From a variety of phenomenological models, a typical range for L can be stated as (70 ± 20) MeV [36][37][38][39][40].…”
Section: The Symmetry Energymentioning
confidence: 99%
“…After years of searching for the density dependence of the symmetry energy, large experimental effort addressing the question through diverse methods, and a multitude of phenomenological (Skyrme or relativistic mean field) models generating correlations among the relevant quantities (see Refs. [9]- [21] for some examples), we would like to reflect on the best way forward given modern predictions and recent constraints, especially those extracted from electroweak scattering experiments.…”
Section: Introductionmentioning
confidence: 99%